A participação da sociedade civil na construção de agenda em torno da nova lei de migração - Gonçalves, Vinícius Raimundo (2024)
The 20th century is more representative than any other in human history of increasingly pronounced demographic flows. In Brazil, where social and political formation is closely linked to these flows, the enactment of the Migration Law (2017) marked the overcoming of the paradigm of national security and nationalism with the adoption of humanitarian principles more in line with the constitutional and conventional commitments assumed by the country. The approval of the law, however, was not the result of a tension free process, but rather was influenced by social movements and civil society actors who managed, as far as possible, to contribute to the elaboration of an avant-gardist legal instrument. The general objective of this work is to describe the Brazilian migration phenomenon and investigate the participation of these interest groups in the construction of agendas around the formulation of the new Migration Law. As specific objectives, the work aims to present the most recent discussions around the themes related to migration and, based on them, to analyze the Brazilian migration profile. Additionally, it seeks to investigate the role of different actors in the legislative construction carried out in the context of the public hearings that preceded the approval and enactment of the law. Finally, it aims to list and analyze the participation of the main social movements identified in the process of drafting the law. The conclusion summarizes the answer to the research question, which asks to what extent the role of social movements impacted the formulation and approval of the new Brazilian Migration Law.